A study of the oxygen and carbon dioxide requirements of thermophilic campylobacters. Issue 7 (July 1983) - Bolton, F J; Coates, D
Abstract : The oxygen and carbon dioxide requirements of different biotypes of thermophilic campylobacters were investigated by means of (a) quantitative studies, and (b) total growth studies. Oxygen tolerance of the five test organisms differed markedly and varied with the carbon dioxide concentration. At most carbon dioxide concentrations tested, Campylobacter jejuni strains NCTC 11168 and NCTC 11392 tolerated 21% oxygen (growth reduced), C coli NCTC 11353 tolerated 15% oxygen (growth reduced), and C jejuni ATCC 3036 and (nalidixic acid resistant thermophilic campylobacter) NCTC 11352 tolerated 10% oxygen (growth not reduced). Total growth studies indicated that 10% oxygen was the optimal concentration for growth of the five test organisms. All exhibited a requirement for carbon dioxide, and only C jejuni strains NCTC 11168 and NCTC 11392 tolerated its absence (growth reduced), when the oxygen concentration was low. The studies indicated that atmospheres containing 5% to 10% oxygen and 1.0% to 10% carbon dioxide are suitable for growth of the various biotypes of thermophilic campylobacters. The oxygen and carbon dioxide concentrations produced in anaerobic jars by variations of the evacuation-replacement technique were determined and suitable practices identified.